2019
DOI: 10.3389/fnut.2019.00077
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Weight Loss Program Improves Body Composition and Metabolic Profile in Adolescents With Obesity: Associations With the Dietary Inflammatory Index

Abstract: Background and Aims: The prevalence of overweight and obesity consitutes a global epidemic and it is growing around the world. Food and nutrition are essential requirements for promoting health and protecting against non-communicable chronic diseases, such as obesity and cardiovascular disease. Specific dietary components may modulate inflammation and oxidative stress in obese individuals. The Dietary Inflammatory Index (DII®) was developed to characterize the anti- and pro-inflammatory effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 66 publications
(61 reference statements)
2
22
0
3
Order By: Relevance
“…Several previous studies showed that integrated multidisciplinary weight-loss programmes, which include the child's family as well, are the most effective [9][10][11]. Reduction of fat mass is associated with normalisation of metabolic parameters, such as inflammatory markers, lipid profile, insulin resistance and arterial blood pressure [12][13][14]. Therefore, early and efficient intervention increases likelihood of staying healthy in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies showed that integrated multidisciplinary weight-loss programmes, which include the child's family as well, are the most effective [9][10][11]. Reduction of fat mass is associated with normalisation of metabolic parameters, such as inflammatory markers, lipid profile, insulin resistance and arterial blood pressure [12][13][14]. Therefore, early and efficient intervention increases likelihood of staying healthy in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, to the best of our knowledge, no studies were carried out in children or adolescents regarding the effects of vitamin D supplementation on body mass reduction during an organized lifestyle modification program. As we presented, adding a 1200 IU/day dose of vitamin D did not lead to higher changes in BMI (BMI centile) or fat mass as well as fat free mass changes in children aged [6][7][8][9][10][11][12][13][14]. It needs to be stated that the results presented show that although there was a reduction in BMI in vitamin D group compared to placebo group (-0.46 ± 1.80 vs. 0.11 ±1.84) and BMI centiles also showed higher reduction in children supplemented with vitamin D (-4.28 ± 8.43 vs. -2.53 ±6.10) none of those results was statistically significant (p = 0.203 and p = 0.319 respectively).…”
Section: Effect Of Vitamin D Supplementation On Body Mass Reductionmentioning
confidence: 53%
“…Several previous studies showed that integrated multidisciplinary weight-loss programs, which include the child's family as well, are the most effective [9][10][11]. Reduction of fat mass is associated with normalization of metabolic parameters, such as inflammatory markers, lipid profile, insulin resistance and arterial blood pressure [12][13][14]. Therefore, early and efficient intervention increases likelihood of staying healthy in the future.…”
mentioning
confidence: 99%
“…Interventionelle bzw. experimentelle Humanstudien, in denen der DII als Tool für eine antiinflammatorische Ernährung genutzt wurde, sind bis dato kaum vorhanden [55][56][57][58][59]. Daher wurden hier hauptsächlich die inzwischen gut ausgearbeiteten Metaanalysen zur Klärung des aktuellen wissenschaftlichen Stands und des Nutzens des DII in Theorie und Praxis herangezogen und sollen im Folgenden eingehender diskutiert werden.…”
Section: Diskussionunclassified
“…Diese Daten besitzen zwar nur eine begrenzte Aussagekraft auf das Entstehungsrisiko verschiedener Erkrankungen, allerdings gehen die Ergebnisse aus den bereits massenhaft untersuchten Datensätzen der Metaanalysen in die überwiegend einheitliche Richtung, dass eine proinflammatorische Ernährungsweise die Risiken erhöhen und bestätigen somit frühere Erkenntnisse. Erfreulicherweise gibt es inzwischen auch ein zunehmendes Interesse daran, den DII in klinischen Interventionsstudien einzusetzen und über eine recht praktische Herangehensweise das Inflammationspotenzial einer Ernährung zu erfassen und anhand dessen die Diät innerhalb der untersuchten Population zu korrigieren [56,57,59]. Demnach könnte der DII bei größer angelegten Interventionsstudien eingesetzt werden, da das Inflammationspotenzial im Allgemeinen und nicht die jeweilige (regionale) Diät als solche evaluiert wird.…”
Section: Diskussionunclassified